2012
DOI: 10.1136/oemed-2011-100316
|View full text |Cite
|
Sign up to set email alerts
|

Associations between radiographic findings and spirometry in a community exposed to Libby amphibole

Abstract: In this large community-based screening cohort, restrictive spirometry is significantly associated with LPT, indicating that this abnormality may result in lung function impairment. Physicians treating patients exposed to Libby amphibole should be aware that LPT may have functional consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…35 A study of urban residents living near a plant using LV also demonstrated an increased risk of pleural changes at lower estimated CFE. 38 Weill and colleagues 39 found that male never smoker Libby residents had a 4.3% and 23.8% loss in percent predicted FVC for LPT and DPT and/or costophrenic angle blunting, respectively. 38 Weill and colleagues 39 found that male never smoker Libby residents had a 4.3% and 23.8% loss in percent predicted FVC for LPT and DPT and/or costophrenic angle blunting, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…35 A study of urban residents living near a plant using LV also demonstrated an increased risk of pleural changes at lower estimated CFE. 38 Weill and colleagues 39 found that male never smoker Libby residents had a 4.3% and 23.8% loss in percent predicted FVC for LPT and DPT and/or costophrenic angle blunting, respectively. 38 Weill and colleagues 39 found that male never smoker Libby residents had a 4.3% and 23.8% loss in percent predicted FVC for LPT and DPT and/or costophrenic angle blunting, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that the LA-induced autoantibodies alone, in the absence of asbestos, could contribute to the fibrotic process in mice (Gilmer et al 2016). The public health significance of this result is further highlighted by evidence that the LA non-malignant pleural disease is more severe and progressive than what is classically described for general occupational (chrysotile) asbestos exposures, and that the radiographic lesions were clearly associated with pulmonary function decline (Black et al 2014, Larson et al 2012, Whitehouse 2004). …”
Section: Introductionmentioning
confidence: 77%
“…Residents of Libby endured exposure to the vermiculite ore contaminated with amphibole asbestos resulting from past industrial production. While pleural disease has been reported most commonly, parenchymal abnormalities have also been reported [37]. …”
Section: Asbestosismentioning
confidence: 99%